# Math help! explain how u did it?

+1 vote
1)-3 3/7 - (-3 1/2) - (+2 1/4)=?

2)0.6-2/3-(-2 1/15)=?

3)(-6.2)- (-2.6)- (-1.6) - 12=?

+1 vote

1 ) - 3 3/7 - (-3 1/2) - (+2 1/4)

= - 3 3/7 + 3 1/2 - 2 1/4

= - 24 /7 + 7 /2 - 9 /4

The LCM of  7, 2 and 4 is 28

= ( -24(4) + 7(14) - 9 (7) ) / 28

= ( - 96 + 98 - 63 ) /28

= - 61 /28 (or) - 2 5/28

- 3 3/7 - (-3 1/2) - (+2 1/4) = -61 /28

3.

Simplify given expression  (-6.2)- (-2.6)- (-1.6) - 12.

Product of two same signs is positive

(-6.2)- (-2.6)- (-1.6) - 12 = -6.2 + 2.6 + 1.6 - 12

Apply commutative property: a + b = b + a

(-6.2)- (-2.6)- (-1.6) - 12 =(-6.2 - 12) + ( 2.6 + 1.6)

(-6.2)- (-2.6)- (-1.6) - 12 = -18.2 + ( 2.6 + 1.6)            (Subtract: -6.2 - 12 = -18.2)

(-6.2)- (-2.6)- (-1.6) - 12 = -18.2 +  4.2                        (Add: 2.6 + 1.6 = 4.2)

(-6.2)- (-2.6)- (-1.6) - 12 = -14

Given expression  (-6.2)- (-2.6)- (-1.6) - 12 = 14.

+1 vote
2) 0.6 -2/3-(-2 1/15)

Given expression = 0.6 - 2/3 -(-2 1/15)

=0.6 - 2/3 -(-29 /15)   (product of to same signs is positive)

=0.6-0.6+29/30           (2/3=0.6)

=0+0.96                     (29/30=0.96)

=0.96

0.6-2/3 -(-2 1/15)=0.96

Simplify given expression  (-6.2)- (-2.6)- (-1.6) - 12.

Product of two same signs is positive

(-6.2)- (-2.6)- (-1.6) - 12 = -6.2 + 2.6 + 1.6 - 12

Apply commutative property: a + b = b + a

=(-6.2 - 12) + ( 2.6 + 1.6)

= -18.2 + ( 2.6 + 1.6)            (Subtract: -6.2 - 12 = -18.2)

= -18.2 +  4.2                        (Add: 2.6 + 1.6 = 4.2)

= -14

Given expression  (-6.2)- (-2.6)- (-1.6) - 12 = -14.

+1 vote
Given expression = 0.6 - 2/3 -(-2 1/15)

=  3/5 -2/3 -(-2 1/15) (desimal change to fraction 0.6=6/10=3/5)

=   3/5 - 2/3 + 31/15

5, 3, 15 L C M is =15

=( 9 - 10 +31) /15

=30 /15

=2

0.6 -2/3  -(-2 1/15)=2